THE EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE: CORPORATE SOCIAL RESPONSIBILITY AS A BUFFER - Musdalifa Musdalifa; Mukhzarudfa Mukhzarudfa; Ratih Kusumastuti (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2022)
This study aims to demonstrate the role of CSR in moderating the influence of corporate governance on financial performance. Furthermore, the researchers compared the corporate governance of Islamic banks in Indonesia and Malaysia. Data analysis used Moderate Regression Analysis and independent t-test analysis. The research data is the financial statements of each Islamic bank in Indonesia and Malaysia from 201 to 2020. This study shows that CSR cannot moderate the financial performance of Indonesian and Malaysian Islamic companies. Another result states that there is no difference in the implementation of corporate governance in Indonesian and Malaysian Islamic banks. CSR is becoming an important aspect of the business community. But does not support the company's financial performance. Nevertheless, this remains a common concern because of the importance of natural sustainability and a balanced economy.